Dietary diversity and its associated factors among rural labourers in South India - Sravani, Settipalli; Lenin, V.; Joshi, Pratibha; Satyapriya,; Ray, Mrinmoy; Bishnoi, Sitaram; Wason, Monika; Punitha, P.; Chowdary, K. Raghavendra; Madhava, M. Chenna; Padigapati, Venkata Naga Sindhuja; Shravani, Kotha; et al. (Frontiers in Nutrition, 2026)
BackgroundMalnutrition continues to be a major global health challenge affecting millions of vulnerable populations across countries. Despite their critical contribution to agricultural productivity, limited evidence exists regarding the dietary diversity and nutritional status of rural labourers in South India. Therefore, the present study aimed to assess dietary diversity and its associated factors among rural labourers in South India.MethodsA community-based cross-sectional study was conducted among 320 rural labourers (men aged 15–54 years and women aged 15–49 years, excluding pregnant and lactating women) and those who were actively engaged in farming and household activities. Respondents were selected using a multistage random sampling method. Data were collected through a structured interview schedule, and the collected data were entered into Excel and analyzed using R Studio (v4.2.2). The dietary diversity score was computed based on the 24-h recall method. Nutritional status was analyzed using the body mass index (BMI), mid-upper arm circumference (MUAC), and calf circumference. Pearson’s chi-squared test was used to determine the association between dietary diversity and nutritional status at a significance level of p < 0.05.ResultsThe findings of this study revealed that the dietary diversity among rural labourers was limited, with heavy reliance on locally available staple foods. In Andhra Pradesh, the majority of men (63.75%) and women (78.75%) had medium dietary diversity; however, men had relatively better diversity, with 21.25% attaining high dietary diversity compared to only 1.25% of women. Comparatively, in Telangana, the majority of men (68.75%) and women (52.50%) were also in the medium dietary diversity category. Although a larger portion of women (30.00%) were in the lowest category, 17.50% of women had high dietary diversity. This reduced the gender gap that existed in Andhra Pradesh. A significant association was observed between dietary diversity and nutritional status of rural labourers (p < 0.05).ConclusionThe study highlighted the low dietary diversity and the existence of undernutrition among rural labourers in South India. This emphasises the need for nutrition education, the promotion of household and community nutrition gardens, and greater awareness of balanced diets, all of which could help improve dietary intake. Furthermore, implementing nutrition and health awareness programmes together with anthropometric indices can aid policymakers in assessing the effectiveness of the Public Distribution System. These efforts can be the basis for the development of targeted interventions that will not only change food consumption patterns but also improve the nutritional status of rural labourers.